Why do people take part in atrial fibrillation screening? Qualitative interview study in English primary care. Issue 3 (16th March 2022) - Hoare, Sarah; Powell, Alison; Modi, Rakesh Narendra; Armstrong, Natalie; Griffin, Simon J; Mant, Jonathan; Burt, Jenni
Abstract : Objectives: There is insufficient evidence to support national screening programmes for atrial fibrillation (AF). Nevertheless, some practitioners, policy-makers and special interest groups have encouraged introduction of opportunistic screening in primary care in order to reduce the incidence of stroke through earlier detection and treatment of AF. The attitudes of the public towards AF screening are unknown. We aimed to explore why AF screening participants took part in the screening. Design: Semistructured longitudinal interview study of participant engagement in the SAFER study (Screening for Atrial Fibrillation with ECG to Reduce stroke). We undertook initial interviews face to face, with up to two follow-up telephone interviews during the screening process. We thematically analysed and synthesised these data to understand shared views of screening participation. Setting: 5 primary care practices in the East of England, UK. Participants: 23 people taking part in the SAFER study first feasibility phase. Results: Participants were supportive of screening for AF, explaining their participation in screening as a 'good thing to do'. Participants suggested screening could facilitate earlier diagnosis, more effective treatment, and a better future outcome, despite most being unfamiliar with AF. Participating in AF screening helped attenuate participants' concerns about stroke and demonstrated their commitment to self-care and being a 'good patient'. Participants felt that the screening test was non-invasive, and they were unlikely to have AF; they therefore considered engaging in AF screening was low risk, with few perceived harms. Conclusions: Participants assessed the SAFER AF screening programme to be a legitimate, relevant and safe screening opportunity, and complied obediently with what they perceived to be a recommendation to take part. Their unreserved acceptance of screening benefit and lack of awareness of potential harms suggests that uptake would be high but reinforces the importance of ensuring participants receive balanced information about AF screening initiatives. Trial registration number: ISRCTN16939438 ; Pre-results.